ANALISIS PRODUKSI DAN PENDAPATAN USAHATANI PETANI PADI RAWA LEBAK SERTA KONTRIBUSINYA TERHADAP PENDAPATAN KELUARGA PETANI DI KELURAHAN GANDUS - Zuliansyah, Muhammad Andri; Putri, Karina Ayu Eka (AGRIPITA JOURNAL, 2018)
The purposes of this research were : (1) to calculate the amount of production and incomes of swampy lowland rice farmers. (2) to calculate off-farm income of swampy lowland rice farmers. (3) to calculate contibution to the family income farmers. The research was conducted in Gandus village. The sampling method used was simple random sampling. Farmers sample of 30 KK swampy lowland rice farmers. The methods of collecting primary data by questionnaire and secondary data from all data related to the research. The result showed that incomes of swampy lowland rice farmers amounted IDR. 2.949,384,45/ha/year. Off-farm income of swampy lowland rice farmers amounted IDR 9.726.000/year. The contribution of swampy lowland rice farmers income amounted 23.27% to the family income of farmers in Gandus village.